ANALISIS TINDAKAN ABORSI ATAS KEHAMILAN AKIBAT PERKOSAAN MENURUT PERSPEKTIF PERLINDUNGAN HUKUM - Christina, Rizky Jayanti; L Elly AM Pandiangan; Lonna Yohanes Lengkong (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Abortion is an act of forcibly removing a fetus which is prohibited in Indonesian laws and regulations, but there are exceptions if the abortion is carried out because of a pregnancy due to being raped. The permissibility of abortion for pregnancy due to rape has caused debate in the community because it is considered not to respect the early life of humans. The research methodology used by the author is normative legal research. This methodology is examining or reviewing laws that are conceptualized as applicable norms or rules by using literature studies in the form of legal books, legislation, research results such as journals, theses, dissertations, legal expert opinions, newspapers and things that related to the subject matter studied. Abortion for pregnancy due to rape is permitted because of the psychological trauma experienced by the victim. Legal protection for rape victims is realized through supervision in the form of pre-action counseling. Rape victims can refuse and get counselour during the pregnancy process so that the rights of the child they are carrying can be fulfilled. The existence of training and licensing for abortion services is a form of legal protection for doctors. The strict procedures for abortion for pregnancy due to rape limit the actions of rape victims and doctors, if they are caught violating the law, the legal impact received is in the form of criminal sanctions. The imposition of sanctions must consider various factors. Therefore, the purpose of sentencing is not only to provide suffering and a deterrent effect, but also to acknowledge the existence of conditions that can alleviate sentencing.